A Survey of Clinical Practices for Hepatocellular Carcinoma Among Experts at Tertiary Hospitals in China From 2020 to 2021 - Hong Zhao; Yilei Mao; Hongguang Wang; Aiping Zhou; Zhengqiang Yang; Yue Han; Gong Li; Xinyu Bi; Chunyi Hao; Xiaodong Wang; Jun Zhou; Chaoliu Dai; et al. (Cancer Innovation)
ABSTRACT Background Hepatocellular carcinoma (HCC) is the second leading cause of cancer‐related death in China. The rapid progress in systemic therapies has led to the approval of many therapeutic methods that have quickly changed clinical guidelines and practices. Because of the high heterogeneity of HCC, there are still some gaps between the guidelines and real‐world clinical practice. The present study surveyed experts in China to investigate the current treatment concepts and clinical practice regarding HCC. Methods A questionnaire survey on the treatment concepts and clinical practice of HCC was administered to 310 experts with senior professional titles in 2020 and 312 experts in 2021. The results were analyzed and compared. Results For treating patients with resectable HCC, 28% of hepatobiliary surgeons indicated neoadjuvant therapy, and 7% chose systemic therapy ± locoregional therapy as 1 L therapy in 2021 compared with 20% and 1% in 2020. More experts chose adjuvant treatment within 1 month in 2021 compared with 2020, and 6 months and 12 months were the leading choices for the duration of adjuvant treatment. In 2021, 79% of surgeons and 19% of interventionalists were willing to conduct downstaging/conversion therapy for patients with potentially resectable HCC, and 78% chose tyrosine kinase inhibitors (TKI) + immunotherapy (IO) + locoregional therapy for cases in which R0 resection could not be achieved. For completely unresectable HCC, more experts preferred TKI + IO‐based therapy as 1 L therapy in 2021 compared with 2020 (78% vs. 55%). The proportion of experts who indicated TKI + IO‐based therapy as 2 L therapy increased from 32% in 2020 to 40% in 2021. Conclusion The survey results indicated that in 2021, compared with 2020, more experts opted to administer IO + TKI for the treatment of liver cancer, and more experts and patients were willing to participate in clinical research.